PERAN PERIKLANAN MEDIA CETAK, DIGITAL MARKETING, DAN KELOMPOK REFERENSI TERHADAP KEPUTUSAN MAHASISWA MEMILIH PERGURUAN TINGGI - Zulia Khairani; Faizah Kamilah; Efrita Soviyanti (Universitas Lancang Kuning, 2022)
This study was conducted to determine and analyze the influence of print media advertising, digital marketing, and reference groups on student decisions to choose colleges. This study conducted a survey on new students at the Lancang Kuning University. The population in this study were 2001 freshmen from the Lancang Kuning university undergraduate program. The sample in this study was 100 students with quota sampling method and then analyzed the data obtained using quantitative and qualitative data analysis. Quantitative analysis includes: validity and reliability test, classical assumption test, multiple regression analysis, hypothesis testing through t test, and analysis of the coefficient of determination (R2). Qualitative analysis is an interpretation of the data obtained in the study and the results of data processing that has been carried out by providing information and explanations. Print media advertising, digital marketing, and reference groups partially and simultaneously have a positive and significant effect on the decision to enroll in college